The integrals in Gradshteyn and Ryzhik. Part 14: An elementary evaluation of entry 3.411.5 - T. Amdeberhan; V. Moll (Scientia Series A: Mathematical Sciences, 2025)
An elementary proof of an entry in the table of integrals by Gradshteyn and Ryzhik is presented.